ROAD CAPACITY AND PARKING GENERATION IN THE SHOPPING CENTER MEGA TOWN SQUARE PALANGKARAYA - Lola Cassiophea (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2016)
The imbalance between the number of vehicles parking and parking off-street parking generation resulted automatically take advantage of the road for parking. From the analysis of the capacity of roads in Mega Town Square on segment Jl. Yos Sudarso, it is known that the level of service is still in accordance with Decree No. KM 14 of 2006, AASHTO, 1973 and Morlok, 1990. On Saturday morning the street value of the service is stable at current low traffic density with a rather high speed but can be controlled by the driver based on the speed limit maximum/minimum and the physical condition of the road. On Saturday afternoon, the traffic density was at a pace that can be controlled by the driver with the value of the service road approaching unstable flow speed of 25 Km/hour. On Saturday night, the traffic density is high enough to speed decreases, and can not be controlled by the driver currents sehinnga restrained. Total vehicle parking per hour is 60 veh/hour. This value is adjusted to supply vehicles going out into the market as much as 100 veh/h. So that parking availability is still sufficient to accommodate the vehicles in the Mega Town Square.